Linguistic and cultural classification of euphemisms in Uzbek and English languages - Usmonova Dono Sotvoldievna; Gulamova Dilnoza Abdillaahat qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Linguocultural aspects of taboo and euphemism as a sign of language and culture are characterized by a new approach. The non-cultural trace is in the nature of the taboo. This cultural trace, if any, is inherent like a euphemism. The contact of these natures finds its place in modern times. We have also investigated the linguocultural aspects of taboo and euphemism in the paper submitted for defense based on materials of different systems of languages. It is a controversial issue that, in contrast to the taboo, the euphemism that replaces it is a cultural and social indicator of society as a linguocultural phenomenon.